Novel design for shifted radiation pattern of rectangular microstrip patch antenna loaded with metamaterial - Nahiyan, Swad Al; Salehin, Ahmed Raisu; Shuvho, D. Golam Mehdy Hassan; Liaqat, Sheikh Minhaj (BRAC University, 2017)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.